THE EFFECT OF APPLICATION OF E- REGISTRATION, E-BILLING, AND E-FILING SYSTEMS ON THE EFFICIENCY OF PERSONAL TAX REPORTING (The Case Study on Individual Taxpayers registered at the Bandung Tegallega Pratama Tax Service Office) - Efriyana, Rika Melya; Amelia, Wulan; Afriyani, Wini; Nurliyanti, Siti; Maidah, Hanim Nimatul; Purnamasari, Dyah (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to determine the effect of implementing e-Registration, e- Billing, and e-Filing systems on the efficiency of individual tax reporting. In line with the research objectives, this research uses quantitative research methods. The wellsprings of information in this exploration are essential information sources got straightforwardly through the distribution of questionnaires. The technique for deciding the example in this exploration is purposive examining. The examination test was selected based on several criteria, there are Individual Taxpayers registered at the Tegallega Pratama Tax Office who have used the tax system with an age range of 18- 40 years as many as 100 respondents. The outcomes showed that the execution of the e-Registration system had no effect on the efficiency of individual tax reporting, while the execution of the e-Charging and e-Recording frameworks affected the effectiveness of individual assessment detailing.